The Effect of Information and Communication Technology Utilization on Taxpayer Compliance with the Ability to Pay as a Variable - Rosyidi, Fahim; Harto, Puji (Borong Newinera Publisher, 2025)
The purpose of this study was to examine the effect of information and communication technology utilization on taxpayer compliance with the ability to pay as a moderating variable. This study uses a quantitative approach. The sample used was 124 taxpayers registered in Semarang City. The Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis technique was used to test the moderating effect of ability to pay and the effect of information and communication technology utilization on taxpayer compliance. The results showed that the use of information and communication technology has a significant positive effect on taxpayer compliance. In addition, this study found that the ability to pay moderates the effect of utilization of information and communication technology on taxpayer compliance.